2015
DOI: 10.1007/s13762-014-0747-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon source on nitrate and ammonium removal from drinking water by immobilised Chlorella sorokiniana

Abstract: The feasibility of alginate-immobilised Chlorella sorokiniana for nitrate and ammonium removal from drinking water in regard to carbon source effects was studied in this paper. Three different natural carbon sources were tested in batch experiments with nitrate as nitrogen source: sucrose, grape juice and acacia honey. The nitrate removal efficiencies achieved at 50 mg/L of initial nitrate concentration under sucrose, grape juice and acacia honey were 93, 99 and 94 %, respectively. At 100 mg/L of nitrate, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Immobilised algal beads were prepared using the procedure described in one of our previous studies, whereby algae-alginate gel suspension (2 % alginate) was dropped into 2 % CaCl 2 solution (Petrovič and Simonič 2015). Prepared beads with diameters in the range of 3.5 ± 0.5 mm (with cell numbers of around 4.5 9 10 5 -cells bead -1 ) were transferred to the algal growth medium and incubated under room conditions for 3-4 days.…”
Section: Algal Culture and Immobilisation Of Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilised algal beads were prepared using the procedure described in one of our previous studies, whereby algae-alginate gel suspension (2 % alginate) was dropped into 2 % CaCl 2 solution (Petrovič and Simonič 2015). Prepared beads with diameters in the range of 3.5 ± 0.5 mm (with cell numbers of around 4.5 9 10 5 -cells bead -1 ) were transferred to the algal growth medium and incubated under room conditions for 3-4 days.…”
Section: Algal Culture and Immobilisation Of Cellsmentioning
confidence: 99%
“…functional groups of the alginate-immobilised algal beads unexposed to metals (Fig. 6, sample a), were examined precisely in our previous study (Petrovič and Simonič 2015), whereby the strongest absorption peak found at 3402 cm -1 corresponded to the -OH stretching of hydroxyls, indicating the presence of these groups on the biosorbent. The region 3600-3300 cm -1 showed, next to the O-H vibrations, the characteristic bands for N-H stretching vibrations, which can be attributed to algal biomass.…”
mentioning
confidence: 91%
“…The corresponding COD removal efficiencies by the end of cultivation were 89.3, 90.6, 91.1, 91.7, 92.9, and 92.7% in FC‐4×, FC‐8×, FR‐4×, FR‐8×, RC‐4×, and RC‐8×, respectively. It was reported that C. sorokiniana had the ability to grow in mixotrophic cultures, where both organic carbon and inorganic carbon could be assimilated concurrently by the algal cells for the synthesis of chemical compositions, such as protein, carbohydrates, chlorophylls, and lipids. Thus, when the mixed wastewaters were used as culture media, this alga would grow in the mixotrophic mode because organic carbon and inorganic carbon were supplied simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Although the biomass productivity of the immobilised algae was lower, the considerable adsorbability of the beads resulted in a higher overall nutrient removal efficiency compared with the suspended algae. The sorption capacity of the alginate for N (16.8 µg/g), P (2.7 µg/g), and OC (4.0 µg/g) showed that the presence of alginate algal beads in the ROC led to adsorption of nutrients by the bead matrix via pore-surface diffusion (Table A1), and hence nutrient removal additional to algal uptake (Wang et al, 1987;Petrovič and Simonič, 2015). Moreover, the negative surface charges on the alginate gel (Table A1) could result in electrostatic adsorption of positively charged organic molecules (Yi et al, 2018), and binding of calcium ions from the alginate beads with the phosphates could promote P removal (Luo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%